A Description of English Language Proficiency and Gender Disparities among Medical Students - Gómez Landeros, Ofelia (2025)
English language proficiency is an asset and a necessity for medical students, allowing them to access the most current scientific information, interact with interntional peers, gain entry into both national and international postgraduate programs, and communicate research findings. Thus, being able to assess English language proficiency among medical students has become highly relevant to medical education. Objective: To assess the English reading skills of medical students at a university in Mexico. Method: A descriptive, observational, and cross-sectional study using a random sample of first-year medical students at a public university was used. The students completed an English Reading Comprehension exam made up of 100 questions. The exam was structured according to the  Common European Framework of Reference for Languages. Results: The observed failure rate was 67.8% with a mean score of 52.5. The following factors were attributed to the student failure rate: Having attended a public high school (OR = 4.3), No English language qualification (OR = 3.73), Studied English only in high school (OR = 3.26) and, Never studied English language (OR = 2.27). Learning English throughout primary and high school is more beneficial that studying it only in primary school (OR = 1.76) or only in high school (OR = 3.26) Conclusion: The low English proficiency level observed in incoming students highlights the need to strengthen English language learning among medical students. The greatest inequalities are associated with access to learning this language in both in primary and secondary schools.